X-ray diffraction results from IODP Hole 386-M0084E - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Results of X-ray diffraction (XRD) analyses from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan, followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. During the onshore phase a set of solid-phase samples, with a volume of approx. 10 cubic centimeters each, were taken with the purpose to be later on split into aliquots for the following three analyses: X-ray diffraction, carbon and X-ray fluorescence. The bulk solid-phase samples were taken from the work halves of core sections at about one sample per meter on average. Unprocessed samples were then shipped to the MARUM - Center for Marine Environmental Sciences of the University of Bremen (Germany), where they were freeze-dried, ground and homogenized to a fine powder (<20 μm particle size) by ECORD Science Operator staff using a pestle and an agate mortar. The aliquots for XRD analysis were prepared with the Philips backloading system in the Crystallography and Geomaterials Research laboratories of the Geoscience Department at the University of Bremen (Germany). X-ray diffractograms were measured on a Bruker D8 Discover diffractometer. Mineral identification and semi-quantification were done using the Philips software X extquotesinglePert HighScore Version 1.2 (Degen et al., 2014, https://doi.org/10.1017/S0885715614000840) and follows concepts of Vogt (2009, https://doi.org/10.2204/iodp.proc.302.203.2009). Minimum relative errors are given based on Vogt et al., 2002 (https://doi.org/10.1346/000986002760833765). Clay Mineral groups are used as sums of multiple minerals. In many samples there is a bulb below 20-25° 2theta pointing to amorphous SiO2, which can be biogenic (e.g. diatoms etc.) or volcanic glass. The bulb size could implicate about 10-20 wt.% of amorphous SiO2. Exact quantification of this component would require more detailed XRD experiments. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023